Socio-Economic Determinants of Consumption Patterns in Thailand - Manajit, Suchita (Animo Repository, 2020)
The purposes of this study were (1) to investigate household consumption patterns, and (2) to investigate how household socioeconomic characteristics contribute to different consumption patterns. The data were obtained from the Household Socio-Economic Survey in the year 2015 by the National Statistical Office of Thailand. The sample consisted of 43,224 households. Cluster analysis was employed to reveal the consumption patterns of households. The relationship between the consumption patterns and household socioeconomics factors was analyzed using logistic regression. The results found five distinctively different consumption. Households with older persons were incorporated in the investigation along with other characteristics of the household, that is, the region of residence, area of residence (municipal or non-municipal area), household arrangement (one person, nuclear, extended, and others), children in the household, older person in the household, sex, marital status, education, work status of household head, and average monthly income of the household. Logistic regression analysis was employed to test the association between household characteristics and consumption patterns, suggesting that household characteristics contributed to consumption patterns. Households with older persons tended to have food-dominated and housing-dominated patterns.